From digitalization to nutrition: the role of digital village construction in shaping dietary intake of rural residents in China - Wang, Jiawei; Kuang, Xia; Wu, Zhihua; Ye, Feng; Liao, Wenmei (Frontiers in Nutrition, 2025)
IntroductionAs China’s dietary structure shifts from “eating enough” to “eating well and eating healthily,” improving the nutritional status of rural residents through digital development has become a key issue for advancing rural revitalization and common prosperityMethodsUsing data from the 2020 China Rural Revitalization Survey (CRRS), this study empirically examines the impact of digital village construction on rural residents’ nutritional intake and its underlying mechanisms.ResultsThe results show that digital village construction significantly improves the nutritional intake of rural residents, with the digital environment playing the most prominent role. Further analysis reveals that digital village construction has the strongest promoting effect on dairy consumption, while its impact is more pronounced in poor villages and non-plain areas, highlighting the importance of digital development in addressing regional disparities and promoting nutritional equity. Mechanism tests indicate that digital village construction improves rural residents’ nutritional intake by enhancing information accessibility, increasing household income, and improving infrastructure.DiscussionBased on these findings, priority should be given to improving network infrastructure, developing rural e-commerce and cold-chain logistics systems, and strengthening the digital dissemination of nutrition and health knowledge, in order to comprehensively enhance the nutritional status of rural residents.